Control of combustion process in an HCCI-DI combustion engine using dual injection strategy with EGR. (1st November 2015) - Das, Pranab; Subbarao, P.M.V.; Subrahmanyam, J.P.
Highlights: HCCI-DI combustion phasing can be controlled by varying premixed ratio and EGR. Peak pressure varies within a narrow range of 2 deg (5–7 deg BTDC). Peak HRR varies within a narrow range of 3 deg (1–4 deg BTDC). A reduction of 76% NO X and 40% smoke emissions are achieved. Abstract: The objective of this study was to achieve a controlled HCCI-DI combustion using in-cylinder dual injection technique and to study the effect of premixed ratio and EGR on combustion, performance and emission characteristics of the engine. Studies were carried out up to 67% (0–67%) of the full load and a constant speed of 1500 rev/min. The premixed ratio was varied from zero to a maximum of 80% of the total fuel by mass. At 50% load condition, occurrences of peak pressure, peak PRR and peak HRR varied within 5–7 deg BTDC, 1.5–5 deg BTDC and 1–4 deg BTDC respectively. It was observed that diesel homogeneous combustion showed a two phase heat release pattern at higher premixed ratios and all combustion parameters advanced dramatically with increasing premixed ratio. The results showed that a reduction of 76% in NO X and 40% in smoke opacity were achieved using 80% premixed ratio with 30% EGR. As the premixed ratio was increased, there was an improvement in IMEP, ISFC and smoke opacity with penalties in HC and CO emissions.